2020
DOI: 10.1249/mss.0000000000002412
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Critical Speed from Raw Training Data in Recreational Marathon Runners

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…In comparison to supervised studies from Gordon et al ( 2017 ) and Hagan et al ( 1987 ), we observed lower weekly mean values in number of workouts, total training duration, and total distance. However, reduced mean values in training volume have also been shown in other unsupervised investigations (Leyk et al, 2009 ; Smyth and Muniz-Pumares, 2020 ). Lower training volumes might be caused by the heterogeneous nature of the larger data set itself.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In comparison to supervised studies from Gordon et al ( 2017 ) and Hagan et al ( 1987 ), we observed lower weekly mean values in number of workouts, total training duration, and total distance. However, reduced mean values in training volume have also been shown in other unsupervised investigations (Leyk et al, 2009 ; Smyth and Muniz-Pumares, 2020 ). Lower training volumes might be caused by the heterogeneous nature of the larger data set itself.…”
Section: Discussionsupporting
confidence: 59%
“…Due to this reasons, Hicks et al ( 2019 ) postulated that a plausibility check of the data from portable sensors is an integral part prior to its analysis. Different publications have already shown the potential of portable sensor data from fitness apps to further improve performance prediction (Altini and Amft, 2018 ; Berndsen et al, 2020 ; Emig and Peltonen, 2020 ), to accurately determine the critical speed of runners and to set up pacing strategies (Smyth and Muniz-Pumares, 2020 ) and also to individualize training plans for marathon preparation (Feely et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, this model can be improved by incorporating additional sources of data, such as heart-rate data, for example, which may facilitate more accurate judgements about whether a runner has hit the wall. Although such data was not available in our dataset, the increasingly widespread adoption of mobile devices, smartwatches, and wearable sensors [55,56] has the capacity to generate large volumes of additional data (heart-rate, cadence, and power), which may be useful in this regard in the future [57,58]. Already, the availability of such diverse sources of data is enabling several new types of health and fitness applications [59][60][61][62][63] and the emergence of powerful new machine learning techniques has been used to support a variety of related prediction and planning tasks in several sporting domains [64][65][66][67][68][69][70][71][72][73] It is also worth noting that the model of the wall analysed here is defined by a pair of parameters-degree of slowdown and length of slowdown-with specific values-0.25 and 5km, respectively-and it is reasonable to question whether the results would be different if different values had been chosen.…”
Section: Limitationsmentioning
confidence: 99%
“…Besides, CS can be estimated using personal best times, which does not require the participant to go to the laboratory (Jones et al, 2019). Finally, a recent study demonstrated that using estimations of CS from raw training data can be sufficient to successfully predict marathon performance and provide useful pacing information (Smyth and Muniz-Pumares, 2020).…”
Section: Discussionmentioning
confidence: 99%